Co-Design of a website for women with pelvic organ prolapse: A study protocol [version 3; peer review: 1 approved, 2 approved with reservations] - Catherine Doody; Cliona O' Sullivan; Carla Perrotta; Brona M Fullen; Maria-Louise Carroll (HRB Open Research, 2024)
Background Despite high reported prevalence of pelvic organ prolapse (POP), women report difficulties accessing evidence-based and reliable information about the condition. Many rely on social media and other popular and highly visible internet platforms which have been found to contain poor quality information that is difficult for the average patient to understand. The aim of the study is to co-design an information website for premenopausal women with POP. The website design will be based on the Website Developmental Model for the Healthcare Consumer (WDMHC) framework. Methods A four phase process will be utilised as per the WDMHC framework: 1) User, task and environmental analysis; 2) Functional and representational analysis; 3) Cognitive walkthrough, keystroke level model, heuristic testing; 4) Content based testing, expert testing and user-based testing. Ethics approval has been obtained (LS-23-19-Carroll-Ful). Two groups of stakeholders will be recruited (i) patient group (ii) healthcare professional (HCP) group. Patient participants will be recruited from an online pelvic floor dysfunction (PFD) support group (n=950 members). A website designer and HCP stakeholders involved in the multidisciplinary team caring for women with POP will be invited to participate. Both groups will participate in separate co-design online workshops. Focus group workshops will be video-recorded, transcribed and imported into NVivo. Themes and subthemes will be developed. The website will be designed and disseminated to all participants for feedback. Cognitive walkthrough and heuristic testing will be undertaken. Following this, necessary modifications will be made to the website. Participants will then complete a modified System Usability Scale (SUS) and the eHealth Impact Questionnaire, while five HCPs will complete the DISCERN instrument. Conclusion This study will inform the design and testing of an information website for women with POP. The website design and content will be informed by patient and HCP stakeholder voices and the health literacy literature.